2002
DOI: 10.1007/s00204-002-0337-7
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Groups of five male and female Wistar rats were treated by gavage with 0, 0.01, 0.05 or 0.2 mg/kg body weight of the known synthetic estrogen ethinylestradiol for 28-32 days according to a modified enhanced OECD Test Guideline no. 407 in order to investigate which of the current and/or additional parameters would detect effects on the endocrine system reliably and sensitively and to provide data on intra-laboratory variability. Two identical studies (A and B) were run concurrently. The modified enhanced protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“… 7 Andrews et al (2002), 127 McLachlan et al (1980), 182 Steinmetz et al (1998), 214 Yuan and Foley (2002)…”
Section: Morphologymentioning
confidence: 99%
“… 7 Andrews et al (2002), 127 McLachlan et al (1980), 182 Steinmetz et al (1998), 214 Yuan and Foley (2002)…”
Section: Morphologymentioning
confidence: 99%
“…We hypothesize that prenatal exposure of oral contraceptive hormones may contribute to ASD development in offspring. Previous studies demonstrate that 10 μg/rat/day EE and 20 μg/rat/day LNG are the lowest individual doses found to inhibit ovulation in intact rodents [ 20 23 ]. In order to find the best dose for the treatment of our dams, we tried two combination doses, with the low dose of 10 μg EE/20 μg LNG and high dose of 30 μg EE/60 μg LNG per rat each day, as recommended by a recent study [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In experiments in adult rats, EE administration induced reductions in reproductive organ weight and fertility dose-dependently 10 , 14 . It has been also reported that exposure to EE in the neonatal 15 and fetal periods 16 , 17 could cause subsequent male infertility or subfertility, raising warnings of its toxicity to humans 18 , 19 . Our present study successfully demonstrated the testicular toxicity of EE even at a lower concentration of 0.01 nM, which indicates that the PC-r method was more sensitive than the AG method as a testicular toxicity test 33 .…”
Section: Discussionmentioning
confidence: 99%